Phycoerythrin extends life span and health span of Caenorhabditis elegans - Sonani, Ravi Raghav (Springer Netherlands, 2014)
In the present study, we tested the antioxidant activity of phycoerythrin (PE, an oligomeric light harvesting protein isolated from Lyngbya sp. A09DM) to curtail aging effects in Caenorhabditis elegans. Purified PE (100 μg/ml) dietary supplement was given to C. elegans and investigated for its anti-aging potential. PE treatment improved the mean life span of wild type (N2)-animals from 15 ± 0.1 to 19.9 ± 0.3 days. PE treatment also moderated the decline in aging-associated physiological functions like pharyngeal pumping and locomotion with increasing age of N2 worms. Moreover, PE treatment also enhanced the stress tolerance in 5-day-aged adults with increase in mean survival rate from 22.2 ± 2.5 to 41.6 ± 2.5 % under thermo stress and from 30.1 ± 3.2 to 63.1 ± 6.4 % under oxidative (hydrogen peroxide)-stress. PE treatment was also noted to moderate the heat-induced expression of human amyloid-beta(Aβ(1-42)) peptide and associated paralysis in the muscle tissues of transgenic C. elegans CL4176 (Alzheimer’s disease model). Effectiveness of PE in expanding the life span of mutant C. elegans, knockout for some up (daf-2 and age-1)- and down (daf-16)-stream regulators of insulin/IGF-1 signaling (IIS), shows the independency of PE effect from DAF-2–AGE-1–DAF-16 signaling pathway. Moreover, the inability of PE in expanding the life span of hsf-1 knockout C. elegans(sy441) suggests the dependency of PE effect on heat shock transcription factor (HSF-1) controlling stress-induced gene expression. In conclusion, our results demonstrated a novel anti-aging activity of PE which conferred increased resistance to cellular stress resulting in improved life span and health span of C. elegans. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11357-014-9717-1) contains supplementary material, which is available to authorized users.